High-speed biomarker identification utilizing porous silicon nanovial arrays and MALDI-TOF mass spectrometry. - Finnskog, D; Jaras, K; Ressine, A; Malm, J; Marko-Varga, G; Lilja, H; Laurell, T (2006)
Speed and accuracy are crucial prerequisites in the application of proteomic methods to clinical medicine. We describe a microfluidic-based nanovial array for rapid proteolytic processing linked to MALDI-TOF MS. This microscale format consumes only minute amounts of sample, and it is compatible with rapid bioanalytical protocols and high-sensitivity readouts. Arrays of vials (300 microm in diameter and 25 microm deep), isotropically etched in silicon wafers were electrochemically porosified. Automated picoliter microdispensing was employed for precise fluid handling in the microarray format. Vials were prefilled with trypsin solution, which was allowed to dry. Porosified and nonporosified nanovials were compared for trypsin digestion and subsequent MS identification of three model proteins: lysozyme, alcohol dehydrogenase, and serum albumin at levels of 100 and 20 fmol. In an effort to assess the rapid digestion platform in a context of putative clinical applications, two prostate cancer biomarkers, prostate-specific antigen (PSA) and human glandular kallikrein 2 (hK2), were digested at levels of 100 fmol (PSA), 20 fmol (PSA) and 8 fmol (hK2). All biomarker digestions were completed in less than 30 s, with successful MS identification in the porous nanovial setting.